A New Model of Multiphonon Excitation Trap-Assisted Band-to-Band Tunneling - Racko, Juraj; Mikolasek, Miroslav; Grmanova, Alena; Breza, Juraj; Benko, Peter; Gallo, Ondrej; Harmatha, Ladislav (Společnost pro radioelektronické inženýrství, 2012)
The paper describes a new approach to calculating the currents in a pn-diode based on the extension of the Shockley-Read-Hall recombination-generation model. The presented theory is an alternative to Schenk’s model of trap-assisted tunneling. The new approach takes into account generation and recombination as well as tunneling processes in pn-junctions. Using this model, the real “soft” I-V curve usually observed in the case of switching diodes and transistors was modeled as a result of the high concentration of traps that assist in the process of tunneling.
Keywords: Shockley-Read-Hall model; Schenk model; trap assisted tunneling; pn-junction; I-V curve